EDUKASI PENTINGNYA MENABUNG SEJAK DINI BAGI ANAK-ANAK DI DESA KOMPANG KABUPATEN SINJAI - Ni'mah, Siar; Normi, Normi (Jurnal Graha Pengabdian, 2024)
Saving is basically setting aside some of today's income to anticipate future needs, both unforeseen and unforeseen. It is very important to teach children and youth the importance of saving from an early age so that they are wiser in spending the money. The purpose of carrying out this activity is to teach children and youth the importance of saving from an early age so that they are wiser in spending the money. In time, they will buy the things they need and when there are things they want they don't have to worry about where they got the money to buy those things. The method used in carrying out this activity is the socialization of activities, giving material about the importance of saving, and the practice of making savings. The result of this educational activity is to make this activity a platform that provides hands-on experience to children and produces work in the form of savings, they are also more able to start managing their personal finances by setting aside some of their pocket money and making their provisions until adulthood. It is hoped that this activity will continue so that children can always get the latest inspiration.